Peran Koperasi Melati Dalam Mendorong Peningkatan Ekonomi Bagi Pelaku Umkm - Riza Rona; Irwanto; Syahira Akmatul Azwa Budi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The role of Micro, Small and Medium Enterprises or more commonly known as UMKM in the economic growth of a country is very important. When the crisis hit in 1998, small and medium scale businesses were relatively able to survive compared to large companies. The research entitled The Role of Jasmine Cooperatives in Encouraging Economic Improvement for Actors. The research objectives are 1) to determine the role of jasmine cooperatives in encouraging economic improvement for UMKM actors, 2) to find out the obstacles faced by jasmine cooperatives. The method used in this research is by using a qualitative approach. The results of the research are: 1) the Melati cooperative located in Syuhada 4 Hamlet, Rantau Seulamat District, East Aceh Regency is the only cooperative that has succeeded in petrifying capital for UMKM actors and participating in boosting the economy. 2) the presence of the jasmine cooperative is expected to always be present in the community and always help in terms of capital with very small returns on services so that it can be of great benefit to the community. 3) there are obstacles that are experienced, namely the existence of members who still have not deposited as their obligations.